2012
DOI: 10.9753/icce.v33.waves.40
|View full text |Cite
|
Sign up to set email alerts
|

Wave Attenuation in Mangrove Forests; Field Data Obtained in Trang, Thailand

Abstract: Mangroves thrive in sheltered intertidal areas in the tropics and sub-tropics. Due to this position at the interface between land and sea, mangroves play an important role in the attenuation of waves. Dissipation of wave energy in mangrove forests is an interesting feature from the viewpoint of coastal protection. Nevertheless, field data are sparse and modeling attempts reveal the need for additional data. This paper presents the results of an extensive field campaign, lasting 6 months, in mangroves along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The transition from mudflat to the pneumatophores 5414 T. Balke et al: Cross-shore gradients of physical disturbance in mangroves of the Avicennia/Sonneratia zone was very abrupt. The Rhizophora zone at all transects was characterised by monospecific stands of mature trees with the characteristic stilt roots (see Horstman et al, 2012). Whereas the pioneer zone at transect B was dominated by mature trees (see , transects A, C and D were dominated by younger trees, smaller than approximately 5 m in height.…”
Section: Field Sites: Transects For Marker Plates and Sediment Propermentioning
confidence: 99%
See 3 more Smart Citations
“…The transition from mudflat to the pneumatophores 5414 T. Balke et al: Cross-shore gradients of physical disturbance in mangroves of the Avicennia/Sonneratia zone was very abrupt. The Rhizophora zone at all transects was characterised by monospecific stands of mature trees with the characteristic stilt roots (see Horstman et al, 2012). Whereas the pioneer zone at transect B was dominated by mature trees (see , transects A, C and D were dominated by younger trees, smaller than approximately 5 m in height.…”
Section: Field Sites: Transects For Marker Plates and Sediment Propermentioning
confidence: 99%
“…dominated zone. The tidal amplitude near the field sites is between 1 and 3 m, and wave measurements by Horstman et al (2012) near transect B and D showed that typical incident wave heights at the mudflat fronting the forest did not exceed 10 cm with wave periods of 3-5 s during the measurement campaign. During a stormy period wave heights of up to 30 cm were measured near transect B .…”
Section: Field Sites: Transects For Marker Plates and Sediment Propermentioning
confidence: 99%
See 2 more Smart Citations
“…Tschirky and Hall [23] and Lima et al [24] performed experiments that indicated that an increase in plant density enhanced the wave dissipation effect. However, Mazda et al [25] and Horstman et al [26] found that when the water depth in the mangrove was more than the height of the aerial roots, an increase in water depth reduced the wave dissipation effect, and when the water depth increased to the height of the mangrove leaves, the wave dissipation effect increased. Cruise and Muslesh [27] used a rigid pole to simulate the emerged portion of rigid vegetation and studied the effect of plant diameter and arrangement on water depth and velocity.…”
mentioning
confidence: 99%